Ultrasound treatment of meat: Effects on quality and potential applicati - Pantuhan, Guillermo P.; Elepa?o, Arnold R.; Castillo-Israe, Katherine Ann T. (Agriculture and Natural Resources, 2024)
Importance of the work: Ultrasound has been recognized as a promising and green emerging technology. However, its ability to really improve existing food processing technologies has not been clearly reported. Objectives: To present current studies on the effects of ultrasound on meat quality as applied in food processing technology systems. Materials and Methods: A systematic review was applied based on a search strategy and analysis of recent research findings on the ultrasound treatment of meat products. The treatment effects on different quality parameters were summarized and potential applications were analyzed. Results: Ultrasound application induced different physical and chemical influences on meat products, with such effects being strengths or weaknesses, depending on the processing technique and the intended meat quality. The underlying mechanism is primarily cavitation which causes degradation of proteins, enlargement of myofibrillar spaces, oxidation reactions, generation of ions and activation of enzymes. Along with microjets, the sponge effect creates microchannels in meat that enables more effective transport of materials into and out of muscle tissues. When proper ultrasound parameters are applied, the treatment can effectively improve the microstructure, pH, water holding capacity, texture, color, anti-microbial properties and sensory attributes of meat products. Main finding: Important parameters must be critically investigated to scale up experimental ultrasound treatments and achieve the target quality in the final products. Most of the recent studies have used ultrasound frequencies in the range 20–55 kHz and power levels in the range 150–600 W. Duration of treatment has varied widely, depending on the type of meat and initial ultrasound settings.